Is Nonlinear Drift Implied by the Short End of the Term Structure? - Takamizawa, Hideyuki (Review of Financial Studies, 2008)
Nonlinear drift models of the short rate are estimated using data on the short end of the term structure, where the cross-sectional relation is obtained by an analytical approximation. The findings reveal that (i) nonlinear physical drift is not implied unless it is strongly affected by cross-sectional dimensions of the data; (ii) nonlinear risk-neutral drift that allows for fast mean reversion for high rates is desirable to explain and predict observed patterns of yield spreads; and (iii) for higher frequency data from which transitory shocks are removed, (ii) still remains valid although the nonlinearity is somewhat reduced. The Author 2007. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please email: journals.permissions@oxfordjournals.org, Oxford University Press.